2011
DOI: 10.1177/1367006911405578
|View full text |Cite
|
Sign up to set email alerts
|

The transfer of V2: inversion and negation in German and Dutch learners of English

Abstract: This article investigates the transfer of verb-second syntax (V2) from L1 German and Dutch into L2 English. A comparative learner corpus analysis between L1 German, Dutch and French, and native English writing reveals that the German and Dutch speakers produce distinct patterns of inversion in declarative clauses, indicating the transfer of V2. They produce non-target subject–auxiliary inversion and copula inversion. However, other reflexes of V2 in interrogatives or with sentential negation are not produced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…As mentioned in Section 1, L1-related differences in various structural and discourse aspects of L2 writing have been well documented in the L2 writing literature (e.g., Carson & Kuehn, 1992;Edelsky, 1982;Jarvis & Crossley, 2012;Lally, 2000;Lefrancois, 2001;Liu, 2008;Rankin, 2012;Uysal, 2008; van Vuuren, Table 5 Mean values and standard deviations of C/T, CT/T, DC/C, and DC/T measurements across different L1 groups. Note: see Table 1 for definitions of C/T, CT/T, DC/C, and DC/T.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As mentioned in Section 1, L1-related differences in various structural and discourse aspects of L2 writing have been well documented in the L2 writing literature (e.g., Carson & Kuehn, 1992;Edelsky, 1982;Jarvis & Crossley, 2012;Lally, 2000;Lefrancois, 2001;Liu, 2008;Rankin, 2012;Uysal, 2008; van Vuuren, Table 5 Mean values and standard deviations of C/T, CT/T, DC/C, and DC/T measurements across different L1 groups. Note: see Table 1 for definitions of C/T, CT/T, DC/C, and DC/T.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, there is already a growing body of literature on L1-related differences in various aspects of L2 writing (e.g., Carson & Kuehn, 1992;Edelsky, 1982;Jarvis & Crossley, 2012;Lally, 2000;Lefrançois, 2001;Liu, 2008;Paquot, 2013;Rankin, 2012;Uysal, 2008;van Vuuren, 2013;van Weijen, van den Bergh, Rijlaarsdam, & Sanders, 2009). Examples of the aspects examined include idea generation (Lally, 2000), information structure (van Vuuren, 2013), rhetoric patterns (Liu, 2008;Uysal, 2008), syntactic structures (Rankin, 2012), and lexical bundles (Paquot, 2013). In a comprehensive review, Lefrançois (2001) reported that in addition to orthographic and lexical knowledge, aspects of grammatical and syntactic processing, general strategies, and cultural schemata in the L1 could all influence L2 writing.…”
Section: Introductionmentioning
confidence: 98%
“…Despite numerous claims within the Initial Hypothesis of Syntax that V2 word order would not transfer into an L2 (e.g., Platzack 2001), many studies have found evidence of considerable and relatively persistent V2 effects in the L2 (e.g., Robertson & Sorace 1999;Westergaard 2003;Bohnacker 2006;Rankin 2012). An important fi nding is that subject-initial and non-subject-initial declaratives behave differently in this respect: In the acquisition of L2 English by Norwegian L1 learners, target-consistent non-V2 word order is in place relatively early in non-subject-initial declaratives, while V-Neg/Adv word order in subject-initial declaratives lasts considerably longer, often into a stage of near-nativeness.…”
Section: Second Language (L2) Acquisitionmentioning
confidence: 99%
“…In L2 and FL acquisition, evidence of L1 syntactic transfer is abundant across learning contexts and across language combinations. For instance, L1 German child and adult learners of English initially transfer the underlying OV (object-verb) word order of German to the L2 (Weigl, 1999;see Sağin-Şimşek, 2006;Sánchez, 2011, for child L2A) and they continue to display persistent transfer of the German verb-second (V2) property in main clauses (Kaltenbacher, 2001;Rankin, 2012;Robertson & Sorace, 1999) as well as in wh-questions and relative clauses (Rankin, 2013(Rankin, , 2014; see also Hopp, 2017).…”
Section: Introductionmentioning
confidence: 99%